Суть і особливості умов формування та забезпечення соціальної безпеки держави - Латишева, О.В.; Ростовський, О.Р.; Алещенко, Р.А.; Васильченко, С.В. (Управління економікою: теорія та практика, 2020)
Визначено суть соціальної безпеки держави та людини, її компоненти та сучасний стан. Встановлено, що засади забезпечення соціальної безпеки закладені на рівні держави, насамперед у законодавчих і нормативно-правових актах, рішеннях Міністерства соціальної політики України, Кабінету Міністрів України та інших органів виконавчої влади, рішеннях місцевих органів виконавчої влади й органів місцевого самоврядування. Визначено граничні значення розвитку суспільства, які вважаються катастрофічними у світовій практиці. Наведено місце України в рейтингу за світовим індексом соціальної мобільності – 2020 (46 місце серед 82 країн) та її соціальні показники. Серед країн-сусідів сьогодні Україна має найменше значення купівельної спроможності. Проаналізовано показники поточного стану соціальної безпеки та чинників впливу порівняно з попередніми роками. Представлено динаміку витрат населення України, його реального наявного доходу та заробітної плати, заборгованості з виплати заробітної плати. Запропоновано використання регресійного аналізу та імітаційного моделювання з метою встановлення найбільш суттєвих чинників впливу на стан і прогнозування динаміки складових соцбезпеки; побудову кореляційно-регресійних моделей на базі існуючої статистичної бази й аналітичних звітів про поточний стан складових соціальної безпеки із застосуванням інструментарію інформаційно-аналітичного забезпечення та імітаційного моделювання. Для підвищення обґрунтованості управлінських рішень щодо розбудови системи соціальної безпеки рекомендовано передбачити можливість удосконалення інформаційно-аналітичного забезпечення. Определены суть социальной безопасности государства и человека, ее компоненты и современное состояние. Установлено, что принципы обеспечения социальной безопасности заложены на уровне государства, прежде всего в законодательных и нормативно-правовых актах, решениях Министерства социальной политики Украины, Кабинета Министров Украины и других органов исполнительной власти, решениях местных органов исполнительной власти и органов местного самоуправления. Определены предельные значения развития общества, которые считаются катастрофическими в мировой практике. Представлено место Украины в рейтинге по мировому индексу социальной мобильности – 2020 (46 место среди 82 стран) и ее социальные показатели. Установлено, что среди стран-соседей сегодня Украина имеет наименьшее значение покупательной способности. Проанализированы показатели текущего состояния социальной безопасности и факторов влияния по сравнению с предыдущими годами. Приведена динамика расходов населения Украины, его реального дохода и заработной платы, задолженности по выплате заработной платы. Предложено использование регрессионного анализа и имитационного моделирования с целью установления наиболее существенных факторов влияния на его состояние и прогнозирование динамики составляющих соцбезопасности; построение корреляционно-регрессионных моделей на базе существующей статистической базы и аналитических отчетов о текущем состоянии составляющих социальной безопасности с использованием инструментария информационно-аналитического обеспечения и имитационного моделирования. Для повышения обоснованности управленческих решений по развитию системы социальной безопасности рекомендуется предусматривать возможность усовершенствования информационно-аналитического обеспечения. The article defined the essence of social security of the state and man, established its constituent components and current state.
The principles of social security are laid down at the state level, primarily in laws and regulations, decisions of the Ministry of Social Policy, the Cabinet of Ministers of Ukraine and other executive bodies, decisions of local executive bodies and local governments.
The limit values of society development, which are considered catastrophic in world practice, have been established. Ukraine's place in the world index of social mobility – 2020 and its social indicators are given. It was found that according to the world index of social mobility, Ukraine in the ranking of 82 countries showed the worst results among neighboring countries and was in 46th place, gaining 61.2 points. It is established that among the neighboring countries today Ukraine has the lowest value of purchasing power.
The indicators of the current state of social security and factors of influence in comparison with previous years are investigated and given, for what the dynamics of incomes and expenses of the population of Ukraine, and also changes of its real disposable income of the population of Ukraine and real wages, dynamics of wage arrears in Ukraine.
The article proposes the use of regression analysis and simulation modeling in order to establish the most significant factors influencing its condition and predict the dynamics of the components of social security. Based on the existing statistical base and analytical reports on the current state of social security components using the tools of information-analytical support and simulation modeling, it is proposed to build correlation-regression models that can be used to predict the current state of social security components.
In order to increase the validity of management decisions on the development of the social security system, it is proposed to provide for the possibility of improving the information and analytical support, for which the possible tools for its implementation are given.